Decomposition of Spontaneous Brain Activity into Distinct fMRI Co-activation Patterns - Liu, Xiao; Chang, Catie; Duyn, Jeff H. (Frontiers in Systems Neuroscience, 2013)
Recent fMRI studies have shown that analysis of the human brain’s spontaneous activity may provide a powerful approach to reveal its functional organization. Dedicated methods have been proposed to investigate co-variation of signals from different brain regions, with the goal of revealing neuronal networks that may serve specialized functions. However, these analysis methods generally do not take into account a potential non-stationary (variable) interaction between brain regions, and as a result have limited effectiveness. To address this, we propose a novel analysis method that uses clustering analysis to sort and selectively average fMRI activity time frames to produce a set of co-activation patterns. Compared to the established networks extracted with conventional analysis methods, these co-activation patterns demonstrate novel network features with apparent relevance to the brain’s functional organization.